Estudo da utilização do short message service na educação a distância: experiência do curso de especialização em saúde da família UNA-SUS/Unifesp - Portugal, Mariana Corrêa Nonato [UNIFESP] (2018)
Objective: This study aims to analyze students' perceptions regarding the use of short messages in the health specialization course of the UNA-SUS / UNIFESP family offered in the distance modality. Materials and methods: This is an exploratory research in which the following instruments were used: a) semi-structured questionnaire to collect information about the participant's profile; and b) semi-open questionnaire for data collection about perceptions of students regarding the experience of using text messages. In addition to these instruments, the secondary information extracted from the Moodle virtual learning environment was used for the students' participation in the course activities during the sending of the text messages. Results Analysis: The results were analyzed based on the qualitative and quantitative approaches. Results: In the conclusion, it was identified that the use of short messages is configured as a resource to support and guide students in distance learning activities.